Central African Republic : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper and Statistical Appendix analyzes economic developments over the past decade in the Central African Republic (CAR). It examines the regional integration efforts of the CAR in the context of the Central African Economic and Monetary Community (CEMAC). The paper presents an overview of the CEMAC customs union reform, and investigates the status of the implementation of the CEMAC trade reform in the CAR. The paper also evaluates the impact of the regional trade reform on the CAR's trade performance, based on trade developments in the CAR during 1994-2002.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet